THE MORPHO-SYNTAX OF ADVERBS IN CHRAMBO - MBU, Martha Njui (International Journal of Arts, Languages, Linguistics and Literary Studies, 2025)
This article seeks to describe the morpho-syntax of adverbs in Chrambo, a Bantoid language spoken by an estimated 29,000 speakers in the village of Bambalang, Ndop Subdivision, Ngoketunjia Division, North West Region of Cameroon. It also aims to contribute to the knowledge of adverbs by providing their description in terms of the morphological structure, functions, and syntax. To achieve this objective, data were obtained from both primary and secondary sources, and the analysis was conducted within a structural framework. The findings reveal that the language has both pure and derived adverbs and are realised by particles, such as [ní jí] “fast", as individual lexical items, through reduplication of words like [shíshí] "well", derived words like "[ní njí] “with strength", and word groups such as [ηgͻhu yua] "last year". It was also observed that the majority of adverb clusters in the language encode meanings related to manner, frequency, magnitude, group size, location, and time. The syntax governing their co-occurrence is constrained by a hierarchical order and is seen as the nature of the interface between them is explained based on their distribution and properties in the language